Fireasy: a tool to aid security policy modeling, translation and understanding firewall configuration - Marinho Queiroz, Leandro Meira [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Eler, Danilo Medeiros [UNESP]; Messias Correia, Ronaldo Celso [UNESP]; Rocha, A.; Bordel, B.; Penalvo, F. G.; Goncalves, R. (Ieee, 2022)
Companies store increasing amounts of data, requiring the implementation of mechanisms to protect them from malicious people. There are techniques and procedures that aim to increase the security of computer systems, such as network protection services, firewalls. They are intended to filter packets that enter and leave a network. Its settings depend on security policies, which consist of documents that describe what is allowed to travel on the network and what is prohibited. The transcription of security policies into rules, written in native firewall language, that represent them, is the main source of errors in firewall configurations. In this work, concepts related to security between networks and firewalls are presented. Related works on security policies and their translations into firewall rules are also referenced. Furthermore, the developed tool, named Fireasy, is presented, which allows the modeling of security policies through graphic elements, and the maintenance of rules written in native firewall language, also representing them in graphic elements. Finally, a controlled experiment was conducted to validate the approach, which indicated, in addition to the correct functioning of the tool, an improvement in the translation of security policies into firewall rules using the tool. In the task of understanding firewall rules, there was a homogenization of the participants' performance when they used the tool.
Keywords: Firewal; firewall rules visualization; SPML2; PacketFilter; security policies